Target loans, current account balances and capital flows: The ECB's rescue facility - Hans-Werner Sinn; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2011)
The Target liabilities of the GIPS countries (Greece, Ireland, Portugal and Spain) amounted to314 billion euros in March 2011. They measure the additional central bank money that their corresponding National Central Banks (NCBs) have loaned in excess of the money needed to cover their domestic currency needs. This additional money was used by the GIPS to pay for a net inflow of goods and assets such as companies, stocks, government bonds or other banking claims.
Keywords: 330